2012
DOI: 10.1039/c2ce25869b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of lanthanide orthovanadate: EuVO4 particles and their fluorescence application

Abstract: Lanthanide orthovanadate erythrocyte-like EuVO 4 particles were obtained via a facile, environmentally friendly hydrothermal process and were demonstrated to have an affinity for histidine (His) and the common protein BSA. Fourier transform infrared (FTIR) and Raman spectroscopy indicated an interaction between EuVO 4 and His, as well as BSA. Due to its unique structure, the anionic group (VO 4 32 ) served to directly combine with His or BSA, while the cation (Eu 3+ ) was used as a stable fluorescent monitor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…It has been concluded that zircon-type EuVO 4 is a valuable red phosphor [3], because it exhibits a strong red emission under both near UV and visible-light excitation. It has also been considered for application in white LEDs [4]; its fluorescence can be used in biology and medicine for monitoring the cells [5]. Potential application has been reported as an ionic conductor [6] and as a material for detection of H 2 O 2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that zircon-type EuVO 4 is a valuable red phosphor [3], because it exhibits a strong red emission under both near UV and visible-light excitation. It has also been considered for application in white LEDs [4]; its fluorescence can be used in biology and medicine for monitoring the cells [5]. Potential application has been reported as an ionic conductor [6] and as a material for detection of H 2 O 2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is used as a fluorescent biological label for the detection of Na+ channel dynamics on cell membranes [77]. EuVO4 might be suitable to track biological systems, such as histidine and bovine serum albumin [78]. …”
Section: The Lanthanide Ions Eu2+/eu3+ and Their Optical Propertiesmentioning
confidence: 99%
“…Au et al synthesized NdVO 4 particles using the citrate method, and their catalytic properties were studied by oxidative dehydrogenation of propane. The effects of Eu3 + doping on morphology and fluorescent properties of neodymium vanadate nanorod-arrays were studied [17,18]. Fan et al synthesized single crystalline tetragonal nanorods of NdVO 4 through hydrothermal method and explained the growth mechanism [19].…”
Section: Introductionmentioning
confidence: 99%